Learners and E-Tutors Experiences of Authentic Assessment in Babcock University Centre for Open Distance and e-Learning - Sotunsa, Mobolanle Ebunoluwa; Agbu, Jane-Frances; Akpa, Emeka; Ogbonna, Ngozi; Akinwunmi, Damilare (West African Journal of Open and Flexible Learning, 2022)
Authentic Assessment (AA) has been heralded as the form of assessment that reflects the real world in classroom learning. Recognising this, the Commonwealth of Learning (COL), in collaboration with the National Universities Commission (NUC) in Nigeria, selected Babcock University among 6 dual-mode universities in Nigeria for sensitisation in, and implementation of Authentic Assessment (AA). Having implemented AA in the second semester of the 2021/2022 academic session at Babcock University Centre for Open Distance and e-Learning (BUCODeL), it becomes imperative for a study to evaluate the impact of the assessment method. This study explores learners’ responses to authentic assessment tasks in five courses designed and delivered over a semester. The survey was designed to compare the learners’ and e-tutors’ preferences for AA over Traditional Assessment (TA) and compare the performance of learners in both assessment methods. Using the survey and Focus Group Discussion methods, findings from the study showed that the learners and e-tutors preferred AA to TA. In addition, the test scores of the learners confirm that their performance is better in the AA courses than in the TA courses. Recommendations from the learners and e-tutors are that courses run on AA be prepared with AA principles and tasks embedded. Additionally, there should be an orientation for learners to familiarize them with AA and continuous training for learners, tutors and other stakeholders.Résumé : L'évaluation authentique (AA) a été présentée comme la forme d'évaluation qui reflète le monde réel dans l'apprentissage en classe. Reconnaissant cela, le Commonwealth of Learning (COL), en collaboration avec la Commission nationale des universités (NUC) au Nigeria, a sélectionné l'Université Babcock parmi 6 universités à double mode au Nigeria pour la sensibilisation et la mise en œuvre de l'évaluation authentique (AA). Ayant mis en œuvre l'AA au second semestre de la session académique 2021/2022 au Centre de l'Université Babcock pour l'apprentissage ouvert à distance et en ligne (BUCODeL), il devient impératif de réaliser une étude pour évaluer l'impact de la méthode d'évaluation. Cette étude explore les réponses des apprenants aux tâches d'évaluation authentiques dans cinq cours conçus et dispensés au cours d'un semestre. L'enquête a été conçue pour comparer les préférences des apprenants et des tuteurs électroniques pour l'AA par rapport à l'évaluation traditionnelle (TA) et pour comparer les performances des apprenants dans les deux méthodes d'évaluation. En utilisant les méthodes de l'enquête et de la discussion en groupe, les résultats de l'étude ont montré que les apprenants et les e-tuteurs préféraient l'AA à l'AT. En outre, les résultats des tests des apprenants confirment que leurs performances sont meilleures dans les cours AA que dans les cours TA. Les apprenants et les tuteurs électroniques recommandent que les cours dispensés sur l'AA soient préparés en intégrant les principes et les tâches de l'AA. En outre, il devrait y avoir une sensibilisation des apprenants pour les familiariser avec l'AA et une formation continue pour les apprenants, les tuteurs et les autres parties prenantes.Mots-clés : évaluation authentique, évaluation traditionnelle, apprentissage ouvert, à distance et en ligne, apprenants et résultats scolaires.
Keywords: Authentic Assessment; Traditional Assessment; Open, distance and e-Learning; learners and academic performance